Quantitative measurement of calcium flux through muscle and neuronal nicotinic acetylcholine receptors - Steven Vernino; Mark V. Rogers; KA Radcliffe; JA Dani (1994)
A new approach was developed to determine quantitatively the fraction of current carried by Ca2+ through an ion channel under physiological conditions. This approach entails the simultaneous measurement of membrane current and intracellular Ca2+ for single cells. Whole-cell patch-clamp techniques were used to measure current, and intracellular Ca2+ was monitored with the fluorescent indicator fura-2. To obtain a quantitative measure of the fraction of current carried by Ca2+, a cell- by-cell calibration method was devised to account for differences among cells in such factors as cellular volume and Ca2+ buffering. The method was used to evaluate the Ca2+ flux through muscle and neuronal nicotinic ACh receptors (nAChRs). In a solution containing 2.5 mM Ca2+ at a holding potential of -50 mV, Ca2+ carries 2.0% of the inward current through muscle nAChRs from BC3H1 cells and 4.1% of the inward current through neuronal nAChRs from adrenal chromaffin cells. The Ca2+ flux through neuronal nAChRs of adrenal chromaffin cells is insensitive to alpha-bungarotoxin. The influx of Ca2+ is voltage dependent, and because of the Ca2+ concentration difference across the cellular membrane, there is Ca2+ influx into the cell even when there is a large net outward current. At both muscle and neuronal cholinergic synapses, activity-dependent Ca2+ influx through nicotinic receptors produces intracellular signals that may have important roles in synaptic development, maintenance, and plasticity.